The Impact Of Digital Inclusive Finance Development On The Income Gap Between Urban And Rural Residents: An Empirical Evidence From Guangdong Province, China - Wu, Wanrong (2024)
This study examines the relationship between urban and rural residents by looking at the impact of digital inclusive finance development on the income gap in GuangDong, China. This study also investigates the impact of the urban-rural income gap between neighboring cities and the impact of digital financial inclusion on reducing the income gap between neighboring cities, for 20 cities in Guangdong, China, over the period of 2010-2020. The study applies the Digital Inclusive Finance Index to examine whether the urban-rural income gap can be reduced. The study uses the Digital Inclusive Finance Index and its three sub-indices as independent variables. The sub-indices are the coverage index, the depth of use index and the degree of digitalization support index. The six dimensions of industrial structure, level of fixed asset investment, government competition, agricultural policy, level of traditional finance, the degree of openness to the world are used as control variables to observe effect of digital inclusive finance on reducing the urban-rural income gap. In addition, the impact of digital inclusion finance on reducing the urban-rural income gap between spatially adjacent cities was also studied. The findings show, in terms of the overall effect, the higher the development level of digital inclusive finance, the stronger the convergence effect on the urban-rural income gap.